Kedudukan Profesi Akuntan Dalam Perwujudan Sustainable Development Goals (SGD’s) 2030 Berbasis Green Technology - Salim Azmal; Hendra Harmain; Yenni Samri Juliati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to identify the accountant's role in the application of green technology in the context of the Sustainable Development Goals (SDG’s). The methodology used in this study was a qualitative method with a literary approach as the foundation for information relating to the Sustainable Development Goals, accountants, and green technology to improve and build human civilization. Changes and developments have persisted to this day. From technological developments to the economy to the standard of living of the people. The development of the world today focuses on the sustainability of environmental protection programs. All existing fields, including health, education, and business, are directed towards sustainability and environmental protection. Green technology is a recent trend that supports environmental sustainability. All industries, even the one usually known as accounting, must use green technologies. The achievement of the 2030 Sustainable Development Goals (SDG’s) program and the role of accountants in day-to-day operations are both discussed in this paper. Keywords: Accountant, SDG’s, Green Technology